The development of WTO law in light of transnational influences: the merits of a causal approach - Messenger, G (2012)
The WTO is one piece in a complex network of international, regional and domestic legal systems and regulatory frameworks. The influences on the development of WTO law extend far beyond its own Members and institutions: domestic legal instruments have provided the inspiration for numerous WTO obligations while the rights and obligations under the covered agreements are frequently incorporated into the legal systems of the Membership. The WTO is home to numerous committees and working groups that also engage with other international bodies and their domestic counterparts. Transnational actors seek to take advantage of these networks, encouraging WTO law to develop in their favour. The interactions involved, however, are highly complex and unpredictable. By drawing on different models of causal explanation, it is possible to offer a perspective on the development of WTO law that accepts its role as part of a larger globalized process. Three different causal influences are identified: instrumental, systemic and constitutive. Together, they offer a prism through which to examine the development of WTO law as it responds to the behaviour of transnational actors, bridging gaps between international relations and law and, it is hoped, offering a convincing explanatory rationale for the way in which WTO law develops.